PENGGUNAAN PINJAMAN MODAL KERJA PADA KOPERASI UNTUK PEMBERDAYAAN EKONOMI USAHA BATIK TULIS DI YOGYAKARTA - Kusuma Chandra Kirana (Jurnal Ekonomi dan Bisnis, 2018)
The purpose of this study is to analyze the Influence of fund on Cooperatie to assist economicempowerment the Business of Batik Writing. The object of research are batik writing owner atdistrict level in Yogyakarta Indonesia. Batik writing business that are members of Cooperatiesample are Yogyakarta City with 60 respondens. Type of data collected is of primary data andsecondary data. Methods of data analysis used in this research include test validity, reliabilitytest and regression analysis. Based on calculation of regression test to funding of capitalvariable is significant to economic empowerment on the business Batik Writing. Thus it can beconcluded that the more effective use of capital loans made by the authors of batik then theireconomic independence is increasing. This means that the economic welfare of the managedbatik business can be achieved.Keywords: Capital Funding, Cooperatie, Economic Empowerment, Batik Writing.